Mike : The Memoirs of the Rt. Hon. Lester B. Pearson, Volume Three: 1957-1968 - Pearson, Lester B. (Book collections on Project MUSE., 2015)
This volume, completed after Pearson's death under the supervision of his son Geoffrey, recounts his involvement in Canadian politics and diplomacy as a MP and Secretary of State for External Affairs during the early years of the Cold War.